2012
DOI: 10.1287/isre.1110.0360
|View full text |Cite
|
Sign up to set email alerts
|

Blog, Blogger, and the Firm: Can Negative Employee Posts Lead to Positive Outcomes?

Abstract: C onsumer-generated media, particularly blogs, can help companies increase the visibility of their products without spending millions of dollars in advertising. Although a number of companies realize the potential of blogs and encourage their employees to blog, a good chunk of them are skeptical about losing control over this new media. Companies fear that employees may write negative things about them and that this may bring significant reputation loss. Overall, companies show mixed response toward negative p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(35 citation statements)
references
References 48 publications
1
32
0
Order By: Relevance
“…Aggarwal et al (2010) find negative posts act as catalyst and can exponentially increase the readership to employee blogs, and this effect is generally enough to offset the negative effect of few negative posts on employee blogs. .…”
Section: Literature Reviewmentioning
confidence: 86%
“…Aggarwal et al (2010) find negative posts act as catalyst and can exponentially increase the readership to employee blogs, and this effect is generally enough to offset the negative effect of few negative posts on employee blogs. .…”
Section: Literature Reviewmentioning
confidence: 86%
“…Existing research on blogs as object of study, the second category identified above, has paid attention to motivations for blogging (e.g., Huang et al, 2007), blog categories (e.g., Dearstyne, 2005), interactions between bloggers and readers (e.g., Huang et al, 2008) and the influence of employee bloggers (e.g., Aggarwal et al, 2011). Madsen (2009) …”
Section: Csr Communications and Bloggingmentioning
confidence: 99%
“…However, evidence from a multitude of sources (e.g. Aggarwal, 2011;Barnes, 2012;Helms, 2010;Jacobs and Nakata, 2010;Munene and Nyaribo, 2013;Piskorski, 2011;Weber, 2011) suggests that organisations have not developed strategies to manage social media. As social media adoption matures, organisations must 'integrate social media strategies with their overall strategy' (Aral et al, 2013: 8).…”
Section: Dominant Problems Associated With Social Media Adoptionmentioning
confidence: 99%
“…Failure to formalise usage policies for internal/external social media use also has unintended consequences (Aggarwal et al, 2011;Bott et al, 2009;Forrester, 2012;Kaplan and Haenlein, 2010;Munene and Nyaribo, 2013;Piskorski, 2011;Ward and Ostrom, 2006). Social media has a 'dark side' that leads to 'abuse, addiction and misuse', reducing productivity, as well as an increasingly 'strained computing and network resource' and 'misrepresentation' due to staff failure to distinguish between personal and business use (Munene and Nyaribo, 2013: 149).…”
Section: Dominant Problems Associated With Social Media Adoptionmentioning
confidence: 99%